2022
DOI: 10.1186/s12864-021-08255-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the coronatine-insensitive 1 (COI1) gene family in response to biotic and abiotic stresses in Saccharum

Abstract: Background The coronatine insensitive 1 (COI1) gene is the core member of jasmonate signaling pathway, which is closely related to plant biotic and abiotic resistance. However, there have been no reports on COI1 in sugarcane (Sacharum spp.). Hence, systematically investigating the characteristics of the COI1 multigene family in sugarcane can provide a means to study and manipulate the jasmonic acid signaling pathway. Results A total of 156 COI1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 92 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…The core members of the JA-signaling pathway, including SCF COI1 (SKP1 + Cdc53/cullin + Rbx1 + F-box) E3 ubiquitin ligase, JAZ repressor proteins, and MYC2 TF, have been defined as the COI1-JAZs-MYC2 module . In our previous study, four key gene families including COI1, allene oxide synthase (AOS), allene oxide cyclase (AOC), and MYC of the JA signaling pathway were genome-wide characterized in sugarcane and indicated that ShCOI1 - 4/5/6 , ShAOS1 , and ScAOC1 genes enhanced sugarcane tolerance to salt, cold, drought, ABA, or S. scitamineum stress, but ShMYC4 negatively regulated the defense response to pathogen stress .…”
Section: Discussionmentioning
confidence: 99%
“…The core members of the JA-signaling pathway, including SCF COI1 (SKP1 + Cdc53/cullin + Rbx1 + F-box) E3 ubiquitin ligase, JAZ repressor proteins, and MYC2 TF, have been defined as the COI1-JAZs-MYC2 module . In our previous study, four key gene families including COI1, allene oxide synthase (AOS), allene oxide cyclase (AOC), and MYC of the JA signaling pathway were genome-wide characterized in sugarcane and indicated that ShCOI1 - 4/5/6 , ShAOS1 , and ScAOC1 genes enhanced sugarcane tolerance to salt, cold, drought, ABA, or S. scitamineum stress, but ShMYC4 negatively regulated the defense response to pathogen stress .…”
Section: Discussionmentioning
confidence: 99%